2007
DOI: 10.1111/j.1365-2427.2007.01743.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for non‐random spatial positioning of migrating smolts (Salmonidae) in a small lowland stream

Abstract: 1. The ontogenetic development of anadromous salmonids includes downstream emigration of immature individuals from freshwater towards the marine environment. Although this migration of juvenile salmonids (smolts) may be associated with severe mortalities, only limited attention has been paid to the spatial positioning of smolts in small streams. 2. Using a novel approach, this study examined the vertical and horizontal positioning of brown trout and Atlantic salmon smolts while performing downstream migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 95 publications
1
38
1
Order By: Relevance
“…Recent studies have demonstrated behavioural avoidance in smolts related to hydraulic conditions (Haro et al 1998;Enders et al 2009), in-stream structures (Kemp and Williams 2008), overhead cover and absence of visual clues (Kemp et al 2005;Kemp and Williams 2009). Moreover, fish guidance may be accomplished using strobe lights (Johnson et al 2005), bubble curtains and sounds (Welton et al 2002;Sonny et al 2006) and deep, mid-channel furrows (Svendsen et al 2007). These findings indicate that smolts can be guided rapidly past the water withdrawal zone and over the weir crest to ensure passage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated behavioural avoidance in smolts related to hydraulic conditions (Haro et al 1998;Enders et al 2009), in-stream structures (Kemp and Williams 2008), overhead cover and absence of visual clues (Kemp et al 2005;Kemp and Williams 2009). Moreover, fish guidance may be accomplished using strobe lights (Johnson et al 2005), bubble curtains and sounds (Welton et al 2002;Sonny et al 2006) and deep, mid-channel furrows (Svendsen et al 2007). These findings indicate that smolts can be guided rapidly past the water withdrawal zone and over the weir crest to ensure passage.…”
Section: Resultsmentioning
confidence: 99%
“…Smith 1982). More recent studies have however, demonstrated smolts responding behaviourally to in-stream structures (Kemp and Williams 2008) and visual clues (Kemp and Williams 2009), avoiding rapidly accelerating currents (Haro et al 1998;Enders et al 2009) and overhead cover (Kemp et al 2005), and preferring certain areas while migrating downstream (Davidsen et al 2005;Svendsen et al 2007). The present study corroborates the conclusion that smolt migration includes active components and depends on behavioural decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect any return of acoustic tagged (and PIT-tagged) individuals into the riverine environment, antennae system can be found in (Svendsen et al, 2007). The PIT-tags antennae were continuously in operation from the beginning of the experiment until September 2012 (approximately 3 years after the last fish were tagged).…”
Section: Smolt Trapping and Trackingmentioning
confidence: 99%
“…Over the past decades, passive integrated transponder (PIT) tags have proven to be a powerful tool for monitoring migration, growth, survival, and spatio-temporal distribution of various fish species [1][2][3][4][5][6]. PIT tags are advantageous due to their longevity, small size, and ability to equip individuals with a unique identification code.…”
Section: Introductionmentioning
confidence: 99%